GATA2 Deficiency Due to de Novo Complete Monoallelic Deletion in an Adolescent With Myelodysplasia. Issue 4 (May 2018) - Vinh, Donald C.; Palma, Laura; Storring, John; Foulkes, William D.
Abstract : GATA2 deficiency is an inherited bone marrow failure syndrome that can manifest with myelodysplasia (myelodysplastic syndrome) with chromosomal aberrations and high risk of evolution to leukemia (particularly, acute myeloid leukemia); immunodeficiency with opportunistic infections; and/or lymphedema. It can be transmitted in families in autosomal-dominant fashion, or present de novo as sporadic disease in adults or children. The authors report a case of an adolescent male with features of GATA2 deficiency resulting from a complete monoallelic deletion, review chromosomal anomalies associated with this disorder, and discuss the management implications.